Pendekatan Kebijakan Formulasi Terhadap Undang-undang Nomor 16 Tahun 2011 Tentang Bantuan Hukum - Nandang Sambas (Faculty of Law, Trisakti University, 2014)
Guarantee the protection of Human Rights (HAM) is given by the state against its citizens is one of the characteristics of a state law. Forms of protection of human nature, among others, lack of access to justice, the legal aid. Normatively there are few laws governing bail justice in the form of legal aid. However, this guarantee is in practice still pose many obstacles. On the basis that the government issued Law no. 16 of 2011 on Legal Aid. An examination of the policy, there is some substance to the Legal Aid Act that need more attention in its implementation in order to not face many obstacles. Kay note: formulation policy, rightbto legal aid.